Toxic Effects of Doxorubicin on Cardiac Dysfuction and Reversal of it by Cassia Absus (Medical Forum Monthly, 2024)
Objective: Cassia absus is a seed for prophylaxis and treatment of cardiac dysfunction induced by Doxorubicin.Study Design: Experimental StudyPlace and Duration of Study: This study was conducted at CMH Institute of Medical Sciences Bahawalpur and Islamia University Bahawalpur from September 2017 to March 2018.Materials and Methods: 70% methanolic (V/V) extract of Cassia absus (Ca.Cr) was prepared under reduced pressure. After development of crude extract for various phytoconstituents, In-vivo pharmacological tests were performed in Wistar albino rats. Animals were divided into six groups. Normal control group, Intoxicated groups, Treatment groups; administered different doses (30, 100 and 300 mg/kg of Ca. Cralong with intoxication) and Standard group. By cardiac puncture blood of each rat was collected after 72 h of Doxorubacin-intoxication, and sera were separated for analysis of (lactate dehydrogenase (LDH), creatinine kinase (CK-MB), aspartate transaminase (AST) and alanine transaminase (ALT)).For histopathology heart/body weight ratio was calculated and hearts were analyzed.Results: By using Anti cancer drug that is Doxorubicin significantly increased the values of serum cardiac biomarkers,become less heart/bodyweight ratios and reveal marked changes in histological findings.Treatment with cassia absus Ca.Cr resulted in significant drop in serum cardiac biomarkersp<0.05),increased heart/bodyweight ratios and histological changesalso showed significant changes.Conclusion: Cassia absus has cadioprotective effects against Doxorubicin on analysis of Cardiac biomarkers and histopathological.